Impact of Clinical Pharmacist Interventions on Medication Reconciliation at Discharge in an Indian Tertiary Care Hospital - Dawaiwala, Idris; Fuse, Monika; Katyari, Manisha; Raut, Shrikant; Shaji, Sharook; Gill, Satyajit Singh; Patwardhan, Vivek (Indian Journal of Pharmacy Practice)
Objectives: Unintentional medication-related discrepancies at discharge are linked to serious Medication Errors (MEs), adverse drug events, and increased healthcare utilization. Given the developmental stage of clinical pharmacy services in India, our study seeks to assess the impact of Clinical Pharmacist (CP) interventions in preventing MEs at discharge within the Indian healthcare setting. Materials and Methods: Conducted at a 350-bed academic Indian tertiary care hospital, this single-centre quasi-experimental study included two phases: a pre-intervention phase (January 2023 to April 2023) and an intervention phase (May 2023 to August 2023). During the pre-intervention period, clinicians alone managed the discharge medication reconciliation process. In the intervention phase, CPs collaborated with doctors. Discharge summaries were reviewed for parameters such as appropriate dosage, weight, creatinine clearance, frequency, administration route, drug timings, duplications, omissions, duration, contraindications, and drug-drug interactions. Results: In the pre-intervention phase, 126 patients (5.6%) had discrepancies, compared to 167 patients (7.7%) in the intervention phase (p=0.6). During the pre-intervention period, only 3 discrepancies (2.3%) were resolved before discharge, while CPs resolved 166 discrepancies (99.4%, p<0.001) during the intervention period, leaving only one discrepancy unresolved. Drug omissions were the most common type of discrepancy in both pre- (97, 66.4%) and intervention (207, 82.8%) groups. The average number of drugs in the discharge summary for patients with discrepancies versus without discrepancy was 8.6 versus 7.5 in the pre-intervention period and 7.6 versus 5.9 (p=0.52) in the intervention period, respectively. Additionally, during the intervention period, the average number of medical specialities involved in patient care for those without discrepancies was 1.5, compared to 2.1 for those with discrepancies (p=0.52). Conclusion: Integrating CPs into the discharge medication reconciliation process significantly reduced drug-related discrepancies. This study highlights the potential of CPs in improving medication and patient safety within the Indian healthcare system.
Keywords: Medication reconciliation; Medication error; Medication safety; Discharge reconciliation; Clinical pharmacy